The Effects of the Newborn Behavioral Observations (NBO) System on Sensitivity in Mother–Infant Interactions. Issue 4 (October 2017) - Nugent, J. Kevin; Bartlett, Jessica Dym; Von Ende, Adam; Valim, Clarissa
Abstract : The Newborn Behavioral Observations (NBO) system is a neurobehavioral observation tool designed to sensitize parents to infants' capacities and individuality and to enhance the parent–infant relationship by strengthening parents' confidence and practical skills in caring for their children. The NBO's focus on relationship building is intended for infant mental health professionals who strive for a relational, family-centered model of care versus a pathology-based model. This study assessed the impact of the NBO on the sensitivity of mother–infant interaction in the first 4 months of life. Primiparous mothers and their full-term infants were randomized into experimental and control groups. The intervention group participated in the NBO in the hospital within 2 days of birth and again at home at 1 month postpartum. At 4 months, dyads ( n = 35) were videotaped during semistructured play episodes, which were coded to assess parent–child sensitivity in interactions with one another. Intervention infants were 2.8 times more likely to be classified as "cooperative" (sensitive) than control group infants. Intervention mothers were 2.5 times more likely to be classified as sensitive than control mothers. These findings highlight the potential of the NBO to promote positive maternal–infant relations by influencing newborn behavior and suggest that the NBO is an effective, time-limited intervention for strengthening relationships between parents and infants.